Inhibition of Glycogen Synthase Kinase 3β Activity in the Basolateral Amygdala Disrupts Reconsolidation and Attenuates Heroin Relapse - Xie, Yuanyang; Zhang, Yingfan; Hu, Ting; Zhao, Zijin; Liu, Qing; Li, Haoyu (Frontiers in Molecular Neuroscience, 2022)
Exposure to a heroin-associated conditioned stimulus can reactivate drug reward memory, trigger cravings for the drug and incduce relapse in heroin addicts. The amygdala, a region of the brain relate to emotions and motivation, involved in environmental cues and appetitive-stimulating behaviors. Recent evidence demonstrates that disrupting the reconsolidation of the heroin drug memories attenuate heroin seeking and underlying neural circuits required for the basolateral amygdala (BLA). Meanwhile, neural functions associated with learning and memory, like synaptic plasticity, are regulated by glycogen synthase kinase 3 beta (GSK-3β). In addition, GSK-3β regulated memory processes, like retrieval of contextual memory and reconsolidation of cocaine-induced memory. Here, we used a heroin intravenous self-administration (SA) paradigm to illustrate the potential role of GSK-3β in reconsolidation of heroin drug memory. Therefore, we used SB216763 as a selectively inhibition of GSK-3β. We found that injecting the seletive inhibitor SB216763 into the BLA, but not the region of the central amygdala (CeA), immediately after heroin-cued memory retrieval disrupted reconsolidation of herion drug memory and significantly attenuated heroin-seeking behavior in subsequent drug-primed reinstatement, suggesting that GSK-3β is critical for reconsolidation of heroin drug memories and inhibiting the activity of GSK-3β in BLA disrupted heroin drug memory and reduce relapse. However, no retrieval or retrieval delay, administration SB216763 into BLA did not alter heroin-seeking behavior in subsequent heroin-primed reinstatement, suggesting that GSK-3β activity is retrieval-dependent and time-specific. More importantly, a long-term effect of SB216763 treatment was observed in a detectable decrease in heroin-seeking behavior, lasting at least twenty-eight days. All in all, this present study demonstrates that the activity of GSK-3β in BLA is required for reconsolidation of herion drug memory. Inhibiting GSK-3β activity of BLA disrupts reconsolidation and attenuates heroin relapse.